Mixed Type I and Type II Collagen Scaffold for Cartilage Repair: Ultrastructural Study of Synovial Membrane Response and Healing Potential versus Microfractures (A Pilot Study). (October 2013) - Enea, D.; Guerra, D.; Roggiani, J.; Cecconi, S.; Manzotti, S.; Quaglino, D.; Pasquali-Ronchetti, I.; Gigante, A.
The association between microfracture of the subchondral plate and a coverage scaffold has emerged as a promising strategy to treat cartilage lesions in a one-step procedure. Between different types of scaffolds (e.g. collagen, hyaluronic acid, polyglycolic acid) currently studied, type I collagen scaffold is the most used for this purpose, and is currently adopted for humans. The aim of this study was to test a novel scaffold made of mixed type I and II collagen (I-IICS) in order to define the immunological reaction of the synovial tissue and the repair capabilities induced by the collagen membrane when associated with microfracture. Eight New Zealand White rabbits, aged 180 days, were operated on bilaterally on the medial femoral condyle. A circular cartilage lesion was performed up to the calcified layer of the medial femoral condyle, and the centre of the lesion was microfractured. Randomly, one of the two lesions was covered with the I-IICS (treated), and the other was left uncovered (control). The synovial membrane reaction and the quality of the cartilage tissue repair were investigated at 2, 90, 180 and 270 days macroscopically, histomorphologically and ultrastructurally. Expression of tumor necrosis factor-alpha (TNF-α) in synovial tissue by immunocytochemistry analyses was also investigated. In the control group, at 2 days gold particles were localized mainly on synoviocyte type A, less on synoviocytes type B and on collagen bundles; in the treated group the reaction is more intense in cells in the matrix, but at 180 days controls and treated joints were very similar. The synovial membranes of the joints receiving the I-IICS did not reveal significant changes compared to the age-matched controls. Signs of inflammation were present at the 90-day time-point, and became less evident at afterwards. The degradation of the scaffolds was already evident at the 90-day time-point. The quality of the cartilage repair of the rabbits treated with the I-IICS was slightly better in 5 cases out of 6 in comparison to the controls. However, a statistically significant difference was not detected (p=0.06). Scaffolds made of mixed type I and II collagen exhibited good biocompatibility properties in vivo and favored cartilage restoration when associated with microfracture, as shown in this pilot study.